Advantage of Crescent Knife in Making Excision of Pterygium (Faridpur Medical College Journal, 2013)
A pterygium is a triangular sheet of fibrovascular tissue which invades the cornea. In the management of pterygium surgical excision is needed. Common practices in pterygium surgery are simple excision, excision with post operative b- radiation or tropical thio-TEPA solution(1:2000) or mitomycin-C solution(0.4%), excision with peroperative use of mitomycin-C or conjunctival autograft or amneotic membrane graft or lamellar keratoplasty of the affected part of the cornea. Recurrence is high in pterygium surgery probably due to facing difficulty for easy and complete separation of fibrovascular growth. So this is a search for new technique where easy smooth and complete separation pterygial tissue can be done with minimum surgical trauma and a good cosmetic look. This study was carried out at Faridpur Medical College Hospital (FMCH) from January 2010 to December 2011. A total 50 cases were selected for study. Technique of operation in all the cases were excision of pterygium with conjunctival autograft. In 50% cases, the head of the pterygium removed from the cornea with crescent knife and in 50% cases the head of the pterygium removed with tooks knife. The follow up period was 12 to 24 months. In the group- A, recurrence occurred in two eyes i.e 8% and succeed in 23 eyes i.e 92%. In the group-B, recurrence occurred in 6 eyes i.e 24% and succeed in 19 eyes i.e. 76%. So, higher success rate and low recurrence rate with good cosmetic look and minimum surgical trauma for those where crescent knife were used. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16888 Faridpur Med. Coll. J. 2013;8(1): 05-06